2018
DOI: 10.1111/ans.14730
|View full text |Cite
|
Sign up to set email alerts
|

Isolated port‐site prostate metastasis after robot‐assisted laparoscopic radical prostatectomy

Abstract: Isolated port-site prostate metastasis after robot-assisted laparoscopic radical prostatectomyThe incidence of port-site metastasis due to tumour seeding in urooncological surgery ranges from 0.09% to 0.73%, which is similar to rates of tumour seeding in open surgery. 1,2 A port-site metastasis is defined as a tumour recurrence localized within the abdominal wall, at or near a laparoscopic trocar entry site, and is not associated with widespread peritoneal carcinomatosis. 3 We present a case of port-site metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In particular PSMA PET/CT was able to show recurrence even with PSA levels of approximately 1 ng/ml. 10,11 In our cases choline PET/CT was performed in all patients and was able to detect port site metastases with PSA ranging from 1.5 to 4.3 ng/ml, but did not reveal peritoneal studding.…”
Section: Discussionmentioning
confidence: 61%
“…In particular PSMA PET/CT was able to show recurrence even with PSA levels of approximately 1 ng/ml. 10,11 In our cases choline PET/CT was performed in all patients and was able to detect port site metastases with PSA ranging from 1.5 to 4.3 ng/ml, but did not reveal peritoneal studding.…”
Section: Discussionmentioning
confidence: 61%
“…A systematic review of port site metastases after robot-assisted surgery revealed histological variance in cases involving surgical device seeding, such as cervical squamous cell carcinoma and adenocarcinomas, gallbladder carcinoma, and urothelial cell carcinoma [11] . Additional primaries associated with port site metastases and seeding events after robot-assisted surgery have been described for renal cell carcinoma, prostate adenocarcinoma, and endometrial carcinoma [4] , [5] , [6] , [7] , [8] , [9] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Case reports described port site and peritoneal seeding after laparoscopic and/or RALP with prostate adenocarcinoma and an undiagnosed case of pancreatic adenocarcinoma. [4] , [5] , [6] , [7] , [8] , [9] However, we present a case report of an unusual peritoneal and port site seeding by an undiagnosed urothelial carcinoma of the bladder after RALP for localized prostate cancer.…”
Section: Introductionmentioning
confidence: 91%
“…[5][6][7][8][9] Of the molecular imaging tools available for prostate cancer, PSMA PET/CT has a clear advantage in detecting early recurrence at lower PSA levels. 5,6 Herein, we illustrate the advantage of the newly Food and Drug Administration-approved PSMA PET ligand 18 F-DCFPyL in identifying such rare patterns of prostate cancer recurrence.…”
mentioning
confidence: 99%
“…Of these, 3 were from their own institution, 9 were identified from a systematic literature review, and 7 cases occurred post–robot-assisted laparoscopic radical prostatectomy 4 . Given its higher sensitivity and specificity, molecular imaging was often the modality to make or suggest the correct diagnosis among case reports of prostate cancer port-site metastasis 5–9 . Of the molecular imaging tools available for prostate cancer, PSMA PET/CT has a clear advantage in detecting early recurrence at lower PSA levels 5,6 .…”
mentioning
confidence: 99%